Converting an Artificial Proto-Language into Data for Testing Computational Approaches in Historical Linguistics (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
This small study shows how data for an artificially created language that was supposed to reflect features of "proto-languages", predating modern languages by several thousand years, can be used in testing computational approaches in historical linguistics. In order to do so,  computational workflow is described that retrieves the data automatically, creating a comparative wordlist compatible in format with software tools for historical linguistics, and then uses a baseline method for automatic cognate detection to compare an artificial language against a sample of Indo-European languages.  The results show that artificial languages might help to fill a gap in testing that has so far been ignored in the literature.
Keywords: constructed language; artificial language; evaluation; Python; Concepticon; computer-assisted language comparison